2022
DOI: 10.1016/j.bbrep.2022.101211
|View full text |Cite
|
Sign up to set email alerts
|

NEIL3-deficient bone marrow displays decreased hematopoietic capacity and reduced telomere length

Abstract: Deficiency of NEIL3, a DNA repair enzyme, has significant impact on mouse physiology, including vascular biology and gut health, processes related to aging. Leukocyte telomere length (LTL) is suggested as a marker of biological aging, and shortened LTL is associated with increased risk of cardiovascular disease. NEIL3 has been shown to repair DNA damage in telomere regions in vitro . Herein, we explored the role of NEIL3 in telomere maintenance in vivo by studying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Similarly, c -MYC promotes hTERT deregulation, resulting in the reduction of telomere length, telomerase activity and cell proliferation [ 82 ]. Additionally, TERT can act as a transcription co-factor that regulates expression of several genes [ 77 ], which are summarized in Supplementary Table S1 [ 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 ,…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, c -MYC promotes hTERT deregulation, resulting in the reduction of telomere length, telomerase activity and cell proliferation [ 82 ]. Additionally, TERT can act as a transcription co-factor that regulates expression of several genes [ 77 ], which are summarized in Supplementary Table S1 [ 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 ,…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other DNA glycosylases, NEIL3 has its structural properties and excels in the repair of bases, including favoring base damage at ssDNA, G-quadruplex, ICLs, replication forks and telomere sites, thus promoting cell cycle progression and cell proliferation. A series of studies have confirmed that Neil3 -/- would probably lead to decreased bone marrow hematopoietic capacity, autoimmune defects, cardiovascular disease (atherosclerosis, myocardial infarction, myocardial rupture) and neurological disorders [ 50 , 96 , 98 , 99 , 102 , 107 ]. On the other hand, unlike NEIL1/2, overexpression of NEIL3, in turn, significantly increased the frequency of mutations in somatic cells; public database analysis also showed that NEIL3 was significantly overexpressed in a variety of cancer tissues or cancer cells, suggesting that NEIL3 may be a carcinogenic gene.…”
Section: Discussionmentioning
confidence: 99%
“…Later, researchers also demonstrated that NEIL3 initiated the BER pathway by recruiting APE1 and POLB to telomeric DNA damage sites primarily during mitosis, which in turn repaired telomere damage [ 49 ]. In vivo experiments revealed that Apoe -/- Neil3 -/- mice had shortened telomeres and reduced telomerase activity in bone marrow cells compared to Apoe -/- mice, as shown by reduced bone marrow production and lower leukocyte levels in peripheral blood [ 50 ]. This study suggests that NEIL3 has a role in protecting the length of telomeres in bone marrow cells in vivo, but the authors did not delve into the specific mechanisms.…”
Section: The Characteristics Of Neil3 For Repairing Oxidative Dna Bas...mentioning
confidence: 99%
“…Firstly, Erdr1 and Mid1 are closely linked in gene mapping, as they are neighbor genes located in the PAR region of the sex chromosomes X and Y in mice (32)(33)(34). Secondly, Mid1 is functionally linked to Erdr1 (19,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52) YAP1 (19,53,54), and YAP1 downstream genes such as CTGF (55), Cry61 (35,40,44,55),36,55), as shown by previous microarray data and experiments. Thirdly, Erdr1 and Mid1 are known to play a shared role in regulating YAP1 signature gene expression (36,55,56).…”
mentioning
confidence: 99%